Cloud service selection: State-of-the-art and future research directions - Sun, L.; Dong, Hai; Hussain, F.; Hussain, O.; Chang, E. (Academic Press, 2014)
Cloud technology connects a network of virtualized computers that are dynamically provisioned as computing resources, based on negotiated agreements between service providers and users. It delivers information technology resources in diverse forms of service, and the explosion of Cloud services on the Internet brings new challenges in Cloud service discovery and selection. To address these challenges, a range of studies has been carried out to develop advanced techniques that will assist service users to choose appropriate services. In this paper, we survey state-of-the-art Cloud service selection approaches, which are analyzed from the following five perspectives: decision-making techniques; data representation models; parameters and characteristics of Cloud services; contexts, purposes. After comparing and summarizing the reviewed approaches from these five perspectives, we identify the primary research issues in contemporary Cloud service selection. This survey is expected to bring benefits to both researchers and business agents. © 2014 Elsevier Ltd.